Intralesional corticotherapy for giant orbital capillary hemangioma - Renato Wendell Ferreira Damasceno (The Pan-American Journal of Ophthalmology)
This study is a retrospective case report of two patients with giant orbital capillary hemangioma who underwent intralesional corticosteroid therapy with three monthly injections of 1 ml triamcinolone acetonide 20 mg/ml. The first case was a 5-month-old female patient with a reddish tumor in her left eye (OS) since birth. The ophthalmological examination revealed normalcy of ocular motility of the right eye (OD) and complete obstruction of the visual axis of the OS. The second one was a 5-month-old male patient with a reddish tumor in his OD since birth. The ophthalmological examination demonstrated complete obstruction of the visual axis of the OD and normalcy of ocular motility of the OS. Both patients underwent three monthly intralesional injections of 1 ml of triamcinolone acetonide 20 mg/ml in a surgical setting under general anesthesia. Both patients evolved satisfactorily, functionally, and esthetically, within the first 3 months of starting treatment. Full recovery was considered with the absence of amblyopia and anisometropia, the preservation of extrinsic and intrinsic ocular motility, and the absence of mass lesion according to clinical and magnetic resonance imaging findings.